From traditional infrastructure to new infrastructure: a new focus of China's Belt and Road Initiative diplomacy?. Issue 3 (4th May 2022) - Zhang, Chuchu; Zhang, Minwei; Xiao, Chaowei
ABSTRACT: Shortly after Beijing proposed the new concept of "new infrastructure", it perceived collaboration in frontier areas such as big data centers, artificial intelligence, and Industrial Internet as a new dimension of the Belt and Road Initiative (BRI). We argue that new infrastructure diplomacy is an extension of China's domestic policy, and a new expedient approach designed to provide a route out of the predicament faced by the BRI. As our spatial statistical analysis of BRI projects shows, while China's cooperation with BRI countries in many new infrastructure sectors may be evolving, it faces enormous challenges in fulfilling its objectives. Beijing's redirecting of its foreign investment priorities from traditional physical infrastructure to high-tech infrastructure triggers increasing concerns from both the BRI countries and world powers, which has been exacerbated in the context of fierce competition between China and the US in the digital sphere. Adding to the challenges are the wide gulfs between the expected market demand and the latter's real market needs for new infrastructure products. Although new infrastructure creates new market opportunities, brings rule-making chances, and diversifies Chinese players in the BRI, it also brings more predicaments than Beijing expected, as it becomes a more politicized topic than traditional physical infrastructure in the international debate.